SYNTHESIS OF THE ISOQUINO-[2,1-c][1,3]-BENZODIAZEPINE DERIVATIVE FROM PAPAVERINE - I Made Sudarma; John Bremner (Indonesian Journal of Chemistry, 2007)
The objective of this research was to synthesize isoquino[2,1-c][1,3]benzodiazepine from papaverine alkaloid. Functional Group Interconversion (FGI) and Carbon -Nitrogen bond connection approach was investigated. Papaverine (1) was nitrated by HNO3 to compound (2) and followed by reduction with Sn and HCl to afford aminonorlaudanosine (3). Formation of cyclic benzodiazepine (4) was achieved by reaction of (3) with CS2. Products of reactions were confirmed by Nuclear Magnetic Resonances (n.m.r), Mass Spectrum, and Fourier Transform Infra Red (FTIR).